Techniques for Locating GPS Jammers using GNU Radio - Sahakyan, M.; Mkhoyan, V.; Sivolenko, E.; Hovhannisyan, B.; Aharonyan, A.; Makarov, S.
Detecting GPS jammers is crucial for ensuring the integrity and reliability of Global Positioning System (GPS) signals, particularly in environments where jamming devices disrupt navigation and communication systems. These jammers emit radio frequency signals that interfere with legitimate GPS signals, leading to significant disruptions. To locate these jammers, advanced techniques such as Angle of Arrival (AOA) and Time Difference of Arrival (TDOA) are utilized. AOA uses phased array antennas to determine the direction of the jamming signal, with algorithms like Multiple Signal Classification (MUSIC) and Minimum Variance Distortionless Response (MVDR) enhancing accuracy. TDOA, on the other hand, triangulates the jammer’s location by measuring the time difference between signal arrival at multiple sensors. The integration of unmanned aerial vehicles (UAVs) equipped with directional antennas and sophisticated algorithms further improves the real-time detection of GPS jammers. These UAVs can cover large areas quickly and provide precise bearing measurements, making them invaluable in both military and civilian applications.
Keywords: GPS; Signal analysis